Eurointegration as a Trigger for the Serbian Ethnic Separatism in Bosnia and Herzegovina - A. M. Ponamareva (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper provides a retrospective analysis of the European Union’s policy towards Bosnia and Herzegovina (BiH) and its possible outcomes for BiH progress towards positive sovereignty amid growing international tensions in the Western Balkans. The paper draws on a vast body of both Russian and Western academic literature on the collapse of Yugoslavia, BiH under the Dayton Agreements, the possibilities of democracy building in divided societies, as well as on a range of official documents adopted by various EU institutions. On that basis the author assesses the prospects for BiH to survive in its current administrative-territorial borders. The paper examines the outcomes of the Bosnian War, as well as the main effects of the external governance mechanisms implementation in BiH. This allows the author to trace the evolution of the EU policy towards BiH and to reassess the country’s progress in terms of Eurointegration. Since the EU has refused to grant countries, which do not meet the Copenhagen criteria, the status of a member state ‘in advance’, the main conclusions on the prospects of the BiH accession to the EU are drawn from the European Commission’s 2020 Report on Bosnia and Herzegovina. Following the logic and the structure of the report, the author assesses the BiH efforts to meet the set targets and criteria, such as establishing a stable democratic political system, promoting the development of civil society institutions and the rule of law, combating corruption and organized crime, ensuring the protection of human rights and freedoms, migration management, strengthening economy and regional cooperation. The report of the European Commission clearly hints that most obstacles for BiH progress towards EU membership arise from the lack of support from the Republika Srpska and that it is impossible to overcome its obstruction within the framework of Dayton Agreements. However, the author argues that this fixation on revision of the Dayton Agreements, accompanied by excessive pressure on the Serbian community in BiH may provoke protective reaction of the Serbian community, resulting in a rising nationalism and disintegration of Bosnia and Herzegovina.